Potential of energy efficiency technologies in reducing vehicle consumption under type approval and real world conditions. (1st December 2017) - Triantafyllopoulos, Georgios; Kontses, Anastasios; Tsokolis, Dimitrios; Ntziachristos, Leonidas; Samaras, Zissis
Abstract: Increasing divergence in fuel consumption and associated carbon dioxide (CO2 ) emissions between certification and in-use levels has called for improvements in passenger car type-approval procedure. The procedure used for vehicle certification in the European Union changes in September 2017. The first objective was to explore whether the new procedure will steer vehicle development into new technology options to reduce CO2 . The second one was to assess the impact of identified technology options in reducing fuel consumption. These questions were addressed employing simulations, using commercially available software, and following validation. With the new procedure, consumption is more sensitive to reductions in inertial, rolling and aerodynamic resistances while engine measures need to be effective over a wider operation range to bring measurable benefits. In all cases, the new procedure better reflected real world conditions than the old one. This is expected to close the gap between in use and certification consumption levels. Implementing new technology options results in overall CO2 reductions for conventional gasoline and diesel cars of 13.9% and 12.7%, respectively. Such rather small improvements make it difficult to reach 2021 targets of 95 gCO2 /km without additional measures. Highlights: Vehicle efficiency technologies potential varies in type approval and real world. New European certification test better reflects in use consumption than old one. Different efficiency gain technologies promoted by new certification test. 11–14% remaining efficiency gains with conventional vehicle technologies.